Análisis estilístico computacional de la novela 2666 de Roberto Bolaño - Henny-Krahmer, Ulrike; Hesselbach, Robert (Perspectives de recherche en linguistique et philologie romanes, 2023)
Keywords: Roberto Bolaño; 2666; Computatioanl literary studies

À propos d’une langue pont: perspectives meta-/sociolinguistiques sur le poitevin-saintongeais - Hesselbach, Robert (Grenzen und Brücken in der Romania - Beiträge zum 35. Forum Junge Romanistik in Innsbruck (18.-20. März 2019), 2022)
La langue régionale du poitevin-saintongeais qui fait l’objet de cet article peut être considérée comme une langue-pont à plusieurs égards : comme langue de transition, elle relie les langues du nord de la zone des langues dʼoïl à celles des langues dʼoc au sud de la France, tandis qu’historiquement son influence a été importante dans la formation du français au Québec et en Acadie dans le Nouveau Monde. Dans cet article, nous présentons les résultats d’une recherche empirique dans le cadre de la sociologie de la langue, qui avait pour but de découvrir l’attitude des membres de la société envers la langue régionale et de se demander dans quelle mesure cette langue régionale contribue à la formation d’une identité (régionale). Les résultats de l’étude par questionnaire présentés ici montrent, pour les différents groupes d’âge, que l’utilisation réelle de la langue est en déclin, mais qu’elle doit être considérée comme une partie de l’identité régionale et donc plutôt comme un bien culturel immatériel qui mérite d’être protég
Keywords: Sprachsoziologie; Regionalsprachen Frankreichs; Poitevin-Saintongeais

Diaphasische Variation und syntaktische Komplexität - Hesselbach, Robert (2019)
This empirically oriented study examines the connection between conceptual orality/literacy and the degree of syntactic complexity in modern European Spanish – and in part, in French. For this purpose, the author syntactically analyzed a stylistically heterogeneous corpus of over 10,000 sentences, both qualitatively and quantitively.<br

Digital Stylistics in Romance Studies and Beyond - Hesselbach, Robert; Calvo Tello, José; Henny-Krahmer, Ulrike; Schöch, Christof; Schlör, Daniel (HeiUP, 2024)
Die digitale Stilistik ist ein Forschungsbereich an der Schnittstelle von Literaturwissenschaft, Linguistik, Digital Humanities und Computational Literary Studies. Sie ist mit der computergestützten und statistischen Analyse des literarischen Stils sowie des Stils im Sprachgebrauch befasst. In diesem Band finden sich Forschungsarbeiten zur digitalen Stilistik aus der Romanistik und darüber hinaus, die zu neuen Methoden und Anwendungen in verschiedenen Sprachkontexten und Literaturen beitragen. Alle Forschungsergebnisse basieren auf der empirischen, computergestützten Analyse literarischer Korpora, die ausgewählt wurden, um Gattungen oder Untergattungen der Lyrik, des Dramas und der Prosa vom 19. bis zum 21. Jahrhundert zu analysiere

El español en América ante los procesos de la globalización - Hesselbach, Robert (Manual del español en América, 2021)
El presente capítulo trata de analizar cómo los procesos de globalización influyen lingüísticamente en las variedades del español en América. Se observa que, dentro de una competición global de lenguas, el «español americano» presenta un fuerte pilar que, como muchas más lenguas en el mundo, adapta en mayor o menor grado préstamos del inglés, la lingua franca de hoy día. No obstante, la situación del español en América se beneficia de la globalización debido al gran número de hispa-nohablantes fuera de España e Hispanoamérica, como por ejemplo en muchas zonas de los Estados Unidos, y a la cantidad de estudiantes que aprenden este idioma como lengua extranjera por razones personales o profesionales.<br
Keywords: globalización; contacto de idioma; anglicismos; unificación del español; aprendizaje del español

Introduction - Hesselbach, Robert; Calvo Tello, José; Henny-Krahmer, Ulrike; Schöch, Christof; Schlör, Daniel (Digital Stylistics in Romance Studies and Beyond, 2024)

Investigating the Relation between Syntactic Complexity and Subgenre Distinction - A Case Study on Two Contemporary French Authors - Hesselbach, Robert (Digital Stylistics in Romance Studies and Beyond, 2024)
The purpose of this article is to explore the ways in which the analysis of the syntactic complexity of a text’s sentences can help distinguish between works belonging to different literary subgenres written by the same author. Based on the considerations of an earlier study (Hesselbach 2019), syntactic complexity is understood here as an array of qualitative as well as quantitative features. Applying this method to a corpus of two contemporary French authors and their novels (1979–2002), comprising both crime fiction (roman policier) and ‘high literature’ (littérature blanche), the results of this study show that syntactic complexity has very little influence on genre distinction, at least for the two subgenres examined. In fact, a very stable distribution of results can be observed in both qualitative and quantitative terms. Furthermore, the evidence suggests that the degree of syntactic complexity is more likely to appear as an author-related characteristic.<br
Keywords: syntactic complexity; (sub)genre distinction; French novel; Yasmina Khadra; Jean Echenoz

Norma, analogía y variación: perspectivas empíricas sobre las formas irregulares del superlativo en español - Goldschmitt, Stefanie; Hesselbach, Robert (Energeia, 2022)
In this paper we address one of the central themes of Eugenio Coseriu's work: the concept and importance of both prescriptive and descriptive norms. Taking as a starting point the irregular forms of the superlative in Spanish, we discuss five adjectives (negro, pobre, libre, célebre and fértil) within the area of tension between norm, variation and analogy and present the results of an empirical acceptability study with Spanish students. The results of the survey show that, at least in the case of the adjectives pobre, libre and célebre, the learned forms of the superlative in -érrimo cannot yet be assumed to have completely disappeared and been replaced by the analogous forms in -ísimo. However, it is indisputable that a linguistic change can be observed, in which the descriptive norm seems to prevai
Keywords: Adjetiv; formas irregulares del superlativo; norma; sistema; analogía; cambio lingüístico; variación lingüística

‹Nous sommes en guerre sanitaire› – A Corpus-based Approach of Official French, Italian and Spanish Social Media Discourse in the Light of the Coronavirus Crisis - Hesselbach, Robert (promptus - Würzburger Beiträge zur Romanistik, 2020)
France, Italy, and Spain are three Romance-speaking countries which – at least in Europe – have been affected to a very high degree by the consequences of the Corona pandemic. This paper examines discursive strategies on social media (Twitter and Facebook) by the three heads of government/state of the aforementioned countries – namely Emmanuel Macron (France), Giuseppe Conte (Italy), and Pedro Sánchez (Spain) – from a corpus-linguistic point of view. For this purpose, a corpus was created which contains all Twitter and Facebook messages posted by these heads of government/state from the beginning of February until the end of April 2020. By applying corpus-linguistic methods we find that all three politicians consciously use social media to sensitize, inform, and – in view of a dramatic pandemic situation – unite their respective populations behind the
Keywords: corpus linguistics; coronavirus; Covid-19; political discourse; social media; lexical co-occurrences

Nuevas perspectivas empíricas sobre una cuestión antigua: la relación entre la complejidad sintáctica y la inmdediatez/distancia comunicativa - Hesselbach, Robert (Was bleibt von kommunikativer Nähe und Distanz? Mediale und konzeptionelle Aspekte sprachlicher Variation, 2021)
This article examines the relation between the degree of syntactic complexity and the communication situation, a relation about which various statements have been made over the years. In contrast to previous research positions (which in many cases are not based on solid data) a sufficiently large corpus comprising of 9,000 sentences of modern European Spanish was compiled for the present study. The qualitative as well as the quantitative analyses show that the oft-postulated gerneralizations “informal communication situation = simple syntax” or “formal communication situation = complex syntax” do not go far enough and must be considered in a more differentiated way, since informal language registers can also be characterized by complex syntactic constructions. Similarly, a predominance of simple sentence constructions can be observed in formal communication situations.<br
Keywords: Syntaktische Komplexität; Nähe- und Distanzsprache; Spanisch; Korpuslinguistik

Reinhard Kiesler (18. Januar 1960–9. September 2015) - Hesselbach, Robert (Zeitschrift für Romanische Philologie, 2016)

Sprachliche Unsicherheit bei unregelmäßigen Superlativbildungen im Spanischen - Goldschmitt, Stefanie; Hesselbach, Robert (Zeitschrift für Romanische Philologie, 2019)
This paper deals with the interrelation between the concept of linguistic insecurity described by Labov (1966) and the irregular formation of Spanish superlatives based on Latin roots such as paupérrimo, celebérrimo etc. instead of the analogue formation pobrísimo or celebrísimo. After a brief overview on the frequency of these forms and their alleged regular equivalents in Spanish corpora, a closer look is taken on the speakers' internal and external aspects of linguistic (in)security. Finally, it is shown by an acceptability test that there are forms on -érrim∗, which are not exclusively restricted to the norma culta in Spanish.
Created from Fastlane, Scopus look-up
Keywords: acceptability judgements; empirical study; irregular forms; linguistic insecurity; Spanish grammar; superlative

Zum historisch-lateinischen Sprachkontakt: Die auf -(ĔR)RIMUS basierende Superlativbildung im Spanischen - Hesselbach, Robert (Romanische Sprachgeschichte und Sprachkontakt, 2022)
At present, the superlative in the Spanish language is formed by the suffix -ísimo (i.e. bueno > buenísimo), which goes back to the classical Latin -ĭssimus. While - ísimo today is stylistically neutral, the eleven adjectives of modern Spanish that form the superlative on -érrimo (< lat. -errimus; i.e. pobre > paupérrimo) show the opposite behavior: they belong ‒ with a few exceptions ‒ rather to an elevated style of language. The aim of this paper is to shed more light on the diachronic development of the forms on -érrimo. By analyzing the CORDE corpus of the Real Academia Española (RAE), it can be shown that at earlier times in the history of the Spanish language, more than the eleven adjectives of present- day Spanish performed suffixations with -érrimo. It is finally argued that not only -érrimo as a superlative marker, but rather the combination of [base + suffix] was borrowed from Classical Latin, and therefore the suffix is productive to a very small extent nowadays.<br
Keywords: Language contact; Morphology; Comparison; Superlativ formation; Spanish; Latin; Spanish language history